KORELASI MENARCHE, PEKERJAAN, USIA MELAHIRKAN DENGAN MENOPAUSE DI BINA KELUARGA LANSIA KECAMATAN KEMANGKON PURBALINGGA - Feti Kumala Dewi (Viva Medika, 2017)
ABSTRACT Background : Pre-menopause and menopausal phase is the phase in which a woman will experience the changes in menstrual patterns, psychological and physical changes. This period occurs between 48 and 65 years of age. The factors that affect the age of menopause are menarche age, occupation and childbirth. These factors can slow the working system of female reproductive organs and also can slow the aging of the body and the occurrence of menopause. Objective : This study aims to Analyzing Correlation Of Menarche, Work, Age Birth With Menopause In Bina Keluarga Lansia Kecamatan Kemangkon Purbalingga. Method : This research is cross sectional research. Sampling technique in this research use accidental sampling, this research sample is mothers in Bina Keluarga Lansia Desa Toyareka as amount 42 people. Bivariant analysis was performed by kolmogorov smirnov test and chi square test. Keywords: menopause, age of menarche, occupation, childbirth